EFL students’ perception on flipped learning in writing class - Akhmad Fauzan; Maria Novary Ngabut (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2018)
This research aims at finding out EFL students’ perceptions on the implementation of Flipped Learning in writing class. Survey research was applied with one-shot design and questionnaire was used to collect data. The setting of this research is at one university in Central Kalimantan Province in Indonesia where English is a foreign language. The students were in their fourth semester learning writing skill. In order to avoid teacher-centered learning which may cause a boring and monotonous classroom, this research implemented Flipped Learning that could change the way students learn. The approach was done during one semester and the questionnaires were then handed out at the end of the semester. After the questionnaires were collected and analyzed quantitatively and qualitatively, the result of this research shows that students had positive perceptions on the implementation of Flipped Learning in Writing 3 class.